Patterning Language Usage and Themes of Problem Formation/Resolution - Koziey, Paul W. (Canadian Journal of Counselling and Psychotherapy, 2011)
This paper outlines a conceptualization and a preliminary exploration of phenomenal patterning, a counselling approach developed by the author, used here in a small group setting to examine how language expression, theme identification, and guided imagery can reveal the basic structure of a person's mindset or worldview. In the present study, patterning focuses specifically on the theme of problem formation/resolution as well as on three universal modelling processes of deletion, generalization, and distortion which were applied in examining linguistic patterns within written protocols. Participants wrote descriptions of their experience in real problem situations and were given a guided imagery exercise in order to amplify the text. Phenomenal patterning was used to identify relatively stable sets of processes — patterns, configurations, sequences of action/ interaction — unrecognized structures carried forward from childhood into adult life.